How We Stopped Worrying about Cyber Doom and Started Collecting Data - Valeriano, Brandon (2018)
Moderate and measured takes on cyber security threats are swamped by the recent flood of research and policy positions in the cyber research field offering hyperbolic perspectives based on limited observations. This skewed perspective suggests constant cyber disasters that are confronting humanity constantly. The general tone of the debate argues that cyber war is already upon us and our future will only witness more cyber doom. However, these hyperbolic perspectives are being countered by empirical investigations that produce the opposite of what is to be expected. It is generally observed that limited cyber engagements throughout the geopolitical system are the dominant form of interaction. Our task here is to offer a different path forward. We first posit what can be known about cyber security interactions with data as well as what cannot. Where is the water’s edge in cyber security research? We then examine the known works in the field that utilize data and evidence to examine cyber security processes. Finally, we conclude with an offering of what types of studies need to be done in the future to move the field forward, away from the prognostication and generalizations so typical in the discourse in this constantly changing and growing field.